2012
DOI: 10.1007/s00412-012-0392-7
|View full text |Cite
|
Sign up to set email alerts
|

Cooperating transcription factors mediate the function of estrogen receptor

Abstract: Estrogen receptor (ER) is a hormone-regulated transcription factor that controls cell division and differentiation in the ovary, breast, and uterus. The expression of ER is a common feature of the majority of breast cancers, which is used as a therapeutic target. Recent genetic studies have shown that ER binding occurs in regions distant to the promoters of estrogen target genes. These studies have also demonstrated that ER binding is accompanied with the binding of other transcription factors, which regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 119 publications
(167 reference statements)
0
18
0
Order By: Relevance
“…Histones are well suited to transmit signals directly to the genome through a plethora of covalent biochemical modifications such as acetylation, phosphorylation, methylation, poly-ADP-ribosylation, ubiquination, and SUMOylation which affect the structure and transcriptional activity of chromatin without altering the DNA sequence. 10,11 Broadly speaking, chromatin exists in two states, (1) the more transcriptionally active, more loosely organized euchromatin, which typically localizes to central regions of the nucleus, and (2) the transcriptionally inactive, more densely packed heterochromatin, which inhabits the nuclear periphery and the area surrounding nucleoli. 12 DNA-binding dyes such as DAPI or Hoechst stain compact heterochromatin darker than its euchromatic counterpart.…”
Section: Overview Of Nuclear Structure and Organizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Histones are well suited to transmit signals directly to the genome through a plethora of covalent biochemical modifications such as acetylation, phosphorylation, methylation, poly-ADP-ribosylation, ubiquination, and SUMOylation which affect the structure and transcriptional activity of chromatin without altering the DNA sequence. 10,11 Broadly speaking, chromatin exists in two states, (1) the more transcriptionally active, more loosely organized euchromatin, which typically localizes to central regions of the nucleus, and (2) the transcriptionally inactive, more densely packed heterochromatin, which inhabits the nuclear periphery and the area surrounding nucleoli. 12 DNA-binding dyes such as DAPI or Hoechst stain compact heterochromatin darker than its euchromatic counterpart.…”
Section: Overview Of Nuclear Structure and Organizationmentioning
confidence: 99%
“…46 In contrast, lamin A undergoes an additional modification, where the protein Zmpste24 removes the farnesylated tail, resulting in mature lamin A. Lamin C, which has a distinct C-terminus, does not undergo the same processing and is not farnesylated. 10 Mature lamin A and lamin C, which lack the hydrophobic farnesyl tail, can be found both in the nucleoplasm and the nuclear lamina. 47 …”
Section: Overview Of Nuclear Structure and Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The proliferative effects of oestrogens in breast cancer cells are mediated through oestrogen receptors, which are ligand-dependent nuclear transcription factors, regulating expression of oestrogen-dependent genes [59]. Studies in a variety of clinical settings have demonstrated the clinical utility of oestrogen receptor as a molecular predictor for hormone response.…”
Section: Oestrogen Receptormentioning
confidence: 99%